Guidelines for Community-Based Innovation and Career Development of Kae Noi Royal Project Member Farmers’ Group - Pongwiritthon, Kajornatthapol; Kamchai, Kamolthip; Chaiyo, Wilaiporn; Srika, Wipawee; Panturee, Walailak; Sawetrattanakul, Sakollawat (Economics and Business Administration Journal Thaksin University, 2024)
The purpose of this study was to study and analyze how participation in Guidelines for Community-Based Innovation and Career Development of Kae Noi Royal Project Member Farmers’ Group affects career change, and self-assessment participants learn to develop career skills in terms of knowledge and skill level assessment. As well as in terms of assessing the level of indirect impact to find the guidelines for the career development scholarship program and the community-based innovation of the Northern Economic Corridor farmers’ group: Kae Noi Royal Project.Determination of sample size using a non-probability sampling method by starting with the technique of quota sampling of 60 people. The convenience sampling method and purposive sampling method were also used in this study. The participants must voluntarily provide information and participate in the project. Data collection using questionnaires and semi-structured interviews through various activities. Data were analyzed using descriptive statistics and content analysis. The results showed that the self-assessment participants learned to develop career skills in the project and had opinions at a high level in all aspects, including the aspect of living and learning with the community and the aspect of the level of indirect impact assessment of project participants.The guidelines for community-based innovation and career development scholarships that the community has accepted knowledge sets (paradigms) should focus on the aspects as follows: 1) K4 keys, which include 1.1) key persons or groups with expertise in the subject, 1.2) Indigenous cultures and cross-cultural gaps, 1.3) social and community products, and 1.4) career and entrepreneur skill courses. 2) I3, which include 2.1) in cash or the sources of funding or budget, 2.2) in kind or the sources of knowledge, and 2.3) in knowledge management. And 3) trust, which is the return of knowledge gained to the community, and information reflection and follow-up “borrowed information and return information to the community”.